2009
DOI: 10.1007/s10522-009-9251-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma copper/zinc ratio: an inflammatory/nutritional biomarker as predictor of all-cause mortality in elderly population

Abstract: Associations have been reported between plasma Cu and Zn levels and the incidence of the most important age-related diseases. Previously proposed methods of using plasma Cu/Zn as a predictor of all-cause mortality have been derived from populations in which old and very old subjects were underrepresented. The purpose of this paper is to estimate the usefulness of plasma Cu/Zn as a sensitive biomarker of harmful inflammatory or nutritional changes in the elderly and its incremental prognostic utility as a predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
118
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 38 publications
16
118
2
2
Order By: Relevance
“…Moreover, the results presented in this manuscript highlight also the higher sensibility of CZr than Cu or Zn alone to general clinical risk conditions in the elderly because these circumstances are generally reflected by a decrease in Zn or by an increase in Cu or both (Belbraouet et al 2007;Ghaemian et al 2011;Malavolta et al 2010).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, the results presented in this manuscript highlight also the higher sensibility of CZr than Cu or Zn alone to general clinical risk conditions in the elderly because these circumstances are generally reflected by a decrease in Zn or by an increase in Cu or both (Belbraouet et al 2007;Ghaemian et al 2011;Malavolta et al 2010).…”
Section: Discussionmentioning
confidence: 63%
“…Our previous findings , in a functional independent population over 81 years, observed a significant risk for mortality in men with levels above 1.78 and women with levels above 2.04 that are substantially lower than the mean values reported in the current sample (1.93 in men and 2.06 in women). However, it is important to consider that the thresholds in Malavolta et al (2010) were calculated from tertiles of a functional independent population where death events were relatively rare (32 deaths after 3.5 years) compared to those reported in this study (145 deaths after 4 years) performed in older people affected by various grade of disease and disability. Therefore, the thresholds identified in this study could potentially display higher clinical relevance than those reported in functionally independent population, taking also into account that clinicians are rarely in contact with healthy and functionally independent elderly, while being usually involved in the clinical management of elderly people with comorbidity and disability.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien no hay consenso, existen estudios que encuentran que los adultos mayores tienen valores de zinc sérico más bajos y de cobre sérico más elevados que los encontrados en adultos jóvenes 3,[20][21][22][23] . Se ha descrito también un aumento de la proporción Cu/Zn séricos en adultos mayores a medida que progresa la edad 24 . La pregunta aún sin resolver es en qué medida esta reducción de los valores séricos de zinc sería consecuencia de los cambios fi siológicos que ocurren durante el envejecimiento, como por ejemplo, la reducción de las masas muscular y ósea, que contienen parte importante del zinc tisular y cuánto se debería a que este grupo etario presenta una mayor frecuencia de procesos infl amatorios y una mayor prevalencia de defi ciencia de zinc.…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified
“…In the elderly, increased Cu/Zn ratio was a predictive factor of mortality and it was associated with reduced serum albumin and increased inflammatory markers, like C-reactive protein and erythrocytes sedimentation rate 12 .…”
Section: Introductionmentioning
confidence: 99%